Overactive Bladder Symptoms Within Nervous System: A Focus on Etiology - Qin, Chuying; Wang, Yinhuai; Gao, Yunliang (Frontiers in Physiology, 2021)
The overactive bladder (OAB) is a common debilitating condition characterized by urgency symptoms with detrimental effects on the quality of life and survival. The exact etiology of OAB is still enigmatic and none of therapeutic approaches seems curative. OAB is generally regarded as a separate syndrome, whereas in clinic OAB symptoms could be found in numerous diseases of other non-urogenital systems, particularly nervous system. The OAB symptoms in neurological diseases are often poorly recognized and inadequately treated. This review provided a comprehensive overview of recent findings related to the neurogenic OAB symptoms. Relevant neurological diseases could be mainly divided into seven kinds as follows: multiple sclerosis and related neuroinflammatory disorders, Parkinson’s diseases, multiple system atrophy, spinal cord injury, dementia, peripheral neuropathy and others. Concurrently, we also summarized the hypothetical reasonings and available animal models to elucidate the underlying mechanism of neurogenic OAB symptoms. Our review highlighted the close association between OAB symptoms and neurological diseases and expanded the current knowledge of pathophysiological basis of OAB. This may increase the awareness of urological complaints in neurological disorders and inspire robust therapies with better outcomes.